Conflict management in transatlantic trade relations: Not every dispute should be subject to the WTO - Stormy-Annika Mildner; Oliver Ziegler (Stiftung Wissenschaft und Politik (SWP), 2009)
In early May this year, one of the longest transatlantic trade rows - the dispute over the European Union's import ban on hormone-treated beef from the United States - was temporarily settled. Given the multitude of trade disputes that could possibly escalate this year - the Airbus-Boeing conflict, the controversy over genetically modified corn, and the 'Buy American' clause - it is worth thoroughly reflecting on the different dispute-settlement fora. The three available institutions - the World Trade Organization (WTO), the Transatlantic Economic Council (TEC), as well as several institutionalised bilateral dialogues on the political and working levels - are not equally suited to address different types of trade conflicts
Keywords: 320